Layout of the First-Mining Working Face in the Protected Seam for Pressure Relief by Peak Stress Shift - Xiao-Xu Gao; Guo-Jin Chai; Guang-An Zhu (Shock and Vibration)
An appropriate layout of the first-mining working face of protected seams is key to rockburst prevention in coal seams. By taking the first-mining working face in the 2-2# middle coal seam in Hulusu Coal Mine as the background, a mechanical model for the stress distribution after mining the upper protective seams was established through theoretical analysis and in situ measurement. The problem concerning the layout of the first-mining working face in the protected seam was transformed into one concerning the optimal horizontal distance L. Furthermore, based on the theory of stress transfer within a semi-infinite plane, the distribution of the vertical stress in the protected seam was deduced, for which numerical simulation was performed. Through calculation, it is best (in terms of roadway excavation) to set L to between 50 and 75 m; the mining-induced disturbance shows the least influence on the two roadways at L = 80 to 140 m and at L = 40 to 100 m, and the influence of the remaining coal pillar on mining of the working face is the least significant. Based on the analytic hierarchy process (AHP) evaluation method, the weights of three groups of contradictory criteria and the weighted values of the peak stress under different values of L were calculated. The results show that the global stress on the first-mining working face in the protected seams is lowest at L = 60 m. The results can provide a reference for the layout of the working faces in protected seams in adjacent coal mines.